Differences in Teacher Locus of Control by Religion, Tolerance, Age, Gender, and Teaching Experience - Afolasade Airat Sulaiman (Kuras Institute, 2023)
This study aims to examine the differences of religious affiliation, tolerance, age, sex, and teaching experience based on the locus of control (LoC) of teachers in Lagos state, Nigeria. The sample for the study consisted of 600 teachers, with 353 female and 247 male participants, aged between 22 and 60 years, and conveniently selected from 20 secondary schools in Lagos State. The study used two instruments: the Adult Nowicki-Strickland Internal-External Control Scale (ANSIE) and the Tolerance Scale (TS). Data was analyzed using simple frequency count, mean, and t-test. Results showed statistically significant differences of age, teaching experience, and tolerance on LoC, but no significant differences of sex and religion. However, the participants’ level of LoC and tolerance were found to be high, at 96.5% and 64.2% respectively. The results of this study provide implications for counselor work with teachers in Lagos state. Based on the findings, it is recommended that counselors consider the impact of age, teaching experience, and tolerance on the locus of control of teachers when working with them. Counselors can also help teachers to further develop their internal locus of control. Additionally, these results could inform counselor education programs, providing guidance on developing the skills necessary to work with teachers and promote locus of control.